The Role of Requirements in the Success or Failure of Software Projects - Hussain, Azham; Mkpojiogu, Emmanuel O.C.; Kamal, Fazillah Mohmad (International Review of Management and Marketing, 2016)
Requirements engineering is pivotal and central to every successful software development project. There are several reasons why software projects fail; however, poorly elicited, documented, validated and managed requirements contribute grossly to software projects failure. Software project failures are normally very costly and risky and these could even a times be life threatening also. Projects that overlook requirements engineering processes often suffer or are most likely to suffer from failures, challenges and other consequent risks. The cost of project failures and overruns when estimated is quite great and grave. In addition, software project failures or overruns portend a challenge in today's competitive market environment. It affects negatively the image, goodwill, profitability, and revenue drive of companies and decreases the marketability of their products, as well as, the perceived satisfaction of their customers and clients (which also leads to poor loyalty). In this paper, requirements engineering was discussed. Its role in software projects success was elaborated. The place of software requirements process in relation to software project failure was explored and examined. Furthermore, project success, challenge and failure factors were also discussed with emphasis placed on requirements factors as they play a major role in software projects' successes, challenges and failures. The paper relied on secondary statistics to explore and examine factors responsible for the successes, challenges and failures of software projects in large, medium and small scaled software companies. Keywords: Requirements Engineering Process, Software Projects, Failure, Success JEL Classifications: L86, M15